Dual Inhibition of Ornithine Decarboxylase and A1 Adenosine Receptor Efficiently Suppresses Breast Tumor Cells - Ma, Hongyan; Li, Qizhang; Wang, Jing; Pan, Jing; Su, Zhengding; Liu, Sen (Frontiers in Oncology, 2021)
Personized treatment of breast cancer is still a challenge, and more treatment options for breast cancer are warranted. Combination therapies have been a highly appreciated strategy for breast cancer treatment in recent years, and the development of new combination therapies could improve patient outcomes. Adenosine and polyamines are both endogenous metabolites with indispensable biological functions. Adenosine binds with the A1 adenosine receptor (A1AR) to downregulate cAMP concentration, and both low cAMP content and high polyamine levels stimulate the growth and proliferation of cancer cells. In this work, we initially used a polyamine synthesis inhibitor, DFMO (α-difluoromethylornithine), and an A1AR inhibitor, DPCPX (8-cyclopentyl-1,3-dipropylxanthine) to investigate if simultaneously inhibiting A1AR and polyamine synthesis has synergistical antitumor effects. Next, we investigated a dual inhibitor (ODC-MPI-2) of A1AR and ODC (ornithine decarboxylase 1), the rate-limiting enzyme in polyamine biosynthesis. We investigated if ODC-MPI-2 could inhibit the proliferation and growth of breast cancer cells. Our data showed that DFMO and DPCPX synergistically inhibit the growth and proliferation of MCF-7 cells. We also demonstrated that ODC-MPI-2 reduces cellular polyamine levels and elevates cAMP concentration. We further showed that ODC-MPI-2 inhibits the growth, proliferation, and migration/invasion of MCF-7 cells. Finally, ODC-MPI-2 showed a preference for inhibiting triple-negative breast cancer cells. The dual inhibition of ODC and A1AR is a new combination therapy strategy for treating breast cancer, and dual inhibitors of ODC and A1AR may be effective future drugs for treating breast cancer.